The effect of hydroxy citric acid supplementation with calorie-restricted diet on metabolic, atherogenic and inflammatory biomarkers in women with non-alcoholic fatty liver disease: a randomized controlled clinical trial. Issue 9 (13th April 2022) - Arefhosseini, Sara; Tutunchi, Helda; Nomi-Golzar, Solmaz; Mahboob, Soltanali; Pouretedal, Zohre; Ebrahimi-Mameghani, Mehrangiz
Abstract : Possible mechanisms of action of hydroxy citric acid (HCA) in the management of NAFLD. Abstract : The objective of the present study was to examine the effects of hydroxy citric acid (HCA) extracts from Garcinia cambogia on metabolic, atherogenic and inflammatory biomarkers in obese women with non-alcoholic fatty liver disease (NAFLD). The present clinical trial was carried out on 40 overweight/obese women with NAFLD. The patients were randomly allocated into either the " HCA group " (receiving calorie-restricted diet (−700 kcal d −1 ) accompanied by HCA tablets) and the " control group " (receiving only calorie-restricted diet) for eight weeks. Weight, height, body mass index (BMI), and waist circumference (WC) were measured. Fasting blood sugar (FBS), lipid profile, liver enzymes, as well as inflammatory biomarkers were determined at baseline and after the intervention. Dietary intake was assessed at baseline and at the end of the trial and food intake data were analyzed by the Nutritionist IV software. Results showed a decrease in energy and macronutrient intake in both groups ( p < 0.05). Weight, BMI, WC, and hip circumference as well as FBS, triglyceride (TG), low-density lipoprotein cholesterol (LDL-C) decreased and high-density lipoprotein cholesterol (HDL-C) increased significantly in the HCA group ( p < 0.05). There were also significant reductions in WC, FBS, TG, total cholesterol, LDL-C in the control group while inter-group changes in FBS, TG, LDL-C and HDL-C were statistically significant. Although atherogenic indices reduced significantly in both groups, inter-group comparison revealed that the HCA group showed greater decrease in the TG/HDL-C ratio than the control group ( p = 0.004). Other atherogenic indices including TC/HDL-C and non-HDL-C/HDL-C ratio showed greater reduction in the control versus HCA group ( p < 0.01). Some inflammatory factors were reduced in the HCA group; however, no significant within- or between-group differences were revealed post-intervention. Our results indicated that HCA supplementation plus calorie-restricted diet could improve some metabolic factors without any significant effect on inflammation in patients with NAFLD.